Attributing the forced components of observed stratospheric temperature variability to external drivers. (3rd February 2016) - Mitchell, D. M.
Abstract : One of the largest anthropogenic fingerprints on climate is observed in stratospheric temperatures, but measurements in this region are uncertain. Here, regularised optimal fingerprinting techniques are used to attribute annual temperature variability in the mid‐upper stratosphere to external forcing factors over the period 1979–2005. Specifically, the solar, volcanic, ozone and greenhouse gas (GHG) forced components are characterised. The analysis compares the two most recent reconstructions of the Stratospheric Sounding Unit (SSU) with each other and with six historically forced simulations taken from the Coupled Model Intercomparison Project, phase 5. In the uppermost stratospheric SSU channel, all individual forcings are detected. Solar and volcanic forcings are also detected in the middle and lower SSU channels, but at these levels the GHG and ozone signals are not detected separately from each other. The uncertainty in the global temperature response due to individual forcings is found to be dominated by observational uncertainty in the upper stratosphere, and the signal‐to‐noise ratio in the middle stratosphere. Estimates of the 11‐year solar cycle amplitude are broadly consistent with reanalysis studies. The temperature response to volcanic eruptions is found to be larger than previously thought in the upper stratosphere (0.4–0.6 K for Mount Pinatubo), although is still dominated by the lower‐stratospheric signal. Finally, the anthropogenic response in the upper stratosphere gives rise to a cooling of ∼2–3 K over the 27‐year period, with two thirds of this attributed to GHGs, and one third to ozone depletion.